(3GdJUQja def YLR Yf GdJCdjas - (3CHhGdbGSe Nda Hf YHGS GdRgQGhj GdWHjH, GdRgQGhj,J (B427 (3g` s
(3ChdgG (B:s
(3HYO GdHSedI GdebGdI GdChd ef cJGH bGd GdMeO ddg QH GdYGdejf CeG HYO GaVd GdYdhe HYO Yde GdOjf hcJGHI GdeHjf Yde GdWH s
(3BNQgG (B:s
(3Yf NGJeI gj GdebGdI GdSJhf ef cJGH GdJUQja s
(3fSNI NRGFfjIs
(3hjLO aj GdeYgO YOI fSN efgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B674s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3eJaQbGJs